Smart Trash System: IoT Innovation in Sustainable Organic Waste Management Based on Zero Waste: Smart Trash System: Inovasi IoT dalam Manajemen Sampah Organik Berkelanjutan Berbasis Zero Waste - Wulan Andang; Raimon Efendi (Perkumpulan Doktor Indonesia Maju (PDIM), 2024)
Organic waste management is still a major challenge in various regions, especially in urban and rural areas that do not yet have an efficient management system. One promising approach is the use of the Internet of Things (IoT) in the Smart Trash system. This study aims to design and implement an IoT-based smart trash system that is able to detect the volume, weight, and composition of organic waste in real-time. Using the prototype method, this system is built with the integration of ultrasonic sensors, weight sensors, and NodeMCU microcontrollers connected to the IoT ThingSpeak platform. The implementation results show that the system is able to provide accurate information and automatic notifications to users when the trash is full or rotting occurs. This system also supports waste sorting from the source, accelerates the recycling process, and supports the zero waste concept. With this technological approach, the community can be encouraged to actively participate in smarter and more sustainable waste management.